Intraoperative Immunostaining for Cytokeratin-7 During Mohs Micrographic Surgery Demonstrates Low Local Recurrence Rates in Extramammary Paget's Disease. Issue 3 (March 2018) - Damavandy, Ali A.; Terushkin, Vitaly; Zitelli, John A.; Brodland, David G.; Miller, Christopher J.; Etzkorn, Jeremy R.; Shin, Thuzar M.; Cappel, Mark A.; Mitkov, Mario; Hendi, Ali
Abstract : BACKGROUND: Extramammary Paget's disease (EMPD) is a rare intraepithelial malignancy with high recurrence rates following standard surgical treatments, ranging from 22% to 60% in large retrospective reviews. OBJECTIVE: To evaluate the local recurrence rate of Mohs micrographic surgery (MMS) supplemented with intraoperative immunohistochemistry for cytokeratin-7 (MMS + CK-7) for primary and recurrent EMPD. MATERIALS AND METHODS: Retrospective, multi-center, cross-sectional study of patients treated using MMS + CK-7. Demographic, clinicopathologic, treatment, and follow-up data were obtained by chart review. RESULTS: The observed local recurrence rate for MMS + CK-7 is 3.3% (2/61 tumors) with a mean follow-up of 43.5 months (1–120 months). Local recurrence occurred in 2.3% (1/43) of primary tumors and 5.6% (1/18) of recurrent tumors. Kaplan–Meier 5-year tumor-free rates are 94.6% overall, 97.1% for primary tumors, and 80.0% for recurrent tumors. The Kaplan–Meier 5-year tumor-free rates for all EMPD tumors treated with MMS + CK-7 versus a historical cohort of MMS alone are 94.6% versus 72.0% ( p = .012). CONCLUSION: MMS + CK-7 is an effective treatment for EMPD, demonstrating improved outcomes compared with historical controls.